THE URGENCY OF PROTECTING THE SAFETY OF JOURNALISTS IN COVERAGING DUTIES ON THE MIDDLE EAST WAR: A CASE STUDY ON THE HAMAS-ISRAEL CONFLICT (Proceedings of the World Conference on Media and Mass Communication, 2024)
The conflict between Hamas and Israel prolonged since 7th October 2023 has caused many reported and unreported casualties from the journalists’ side.  Until March 2024, 105 media workers from various countries were killed while covering events in the Gaza Strip. The number of casualties has risen exceedingly since the year 2022. The International Federation of Journalists (IFJ) reported the deaths of journalists in the Gaza Strip had contributed to 72% of the deaths of all media workers worldwide. The death toll of journalists in the Gaza Strip in the context of the Israel-Hamas conflict constitutes an unresolved problem threatening the freedom of the press and democracy. This study aims to excavate what efforts should be made by relevant authorities to protect the safety of journalists so that they can avoid violence when covering and disseminating information in conflict areas, especially in the Gaza Strip.  This study uses a qualitative approach.  Data collection was conducted through a literature study and content analysis of news articles on violence against journalists during war coverage in the Gaza Strip. The research findings show that the relevant authorities have only expressed concern about the violence and deaths of journalists in Gaza but there has been no concrete effort to guarantee the protection of journalists. A concerted effort to protect journalists in dangerous environments such as war zones is essential to uphold democratic values and encourage transparent information dissemination despite challenging situations.
Keywords: On Duty Journalist; Effective and Optimal State Protection; Freedom of the Press; Hamas-Israel conflict